2003
DOI: 10.1074/jbc.m212425200
|View full text |Cite
|
Sign up to set email alerts
|

Activin A Signaling Induces Smad2, but Not Smad3, Requiring Protein Kinase A Activity in Granulosa Cells from the Avian Ovary

Abstract: Activin A signaling is an important regulator of ovarian granulosa cell function. The cytosolic signal transducer Smad2 is most highly expressed in chicken granulosa cells (cGC) of preovulatory follicles. Moreover, Smad2 shows predominant nuclear localization in freshly isolated cGC, indicating active Smad signaling in vivo. Primary cGC cultured in vitro require activin A to sustain high Smad2 levels, which otherwise drop dramatically in the absence of activin A. This activin A-dependent Smad2 expression is ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 50 publications
1
23
1
Order By: Relevance
“…There is a significant increase in the theca content of activin A found within the most recently selected (9-mm-diameter) follicle [16], suggesting the potential for paracrine signaling at the time of follicle selection. Moreover, avian homologs to type I and type II TGF␤ and activin receptors as well as their associated cell signaling components (Smad2, 3, 4, and 7) have been identified [17, 18; GenBank accession AF230192], and several of these have been described within hen granulosa cells [19][20][21]. Such findings support the possibility of a paracrine and/or autocrine function for activin and TGF␤ within hen follicles.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…There is a significant increase in the theca content of activin A found within the most recently selected (9-mm-diameter) follicle [16], suggesting the potential for paracrine signaling at the time of follicle selection. Moreover, avian homologs to type I and type II TGF␤ and activin receptors as well as their associated cell signaling components (Smad2, 3, 4, and 7) have been identified [17, 18; GenBank accession AF230192], and several of these have been described within hen granulosa cells [19][20][21]. Such findings support the possibility of a paracrine and/or autocrine function for activin and TGF␤ within hen follicles.…”
Section: Introductionmentioning
confidence: 72%
“…Previously published data demonstrate that activin A treatment promotes Smad2 phosphorylation and nuclear translocation in hen granulosa cells from preovulatory follicles [21]. Additionally, both FSH and TGF␤ can upregulate levels of smad2 (but not smad3) mRNA expression [19,21].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In vivo, Smad2 and Smad3 show differential expression in rat estrous cycle, Smad2 expression, but not Smad3, is observed in luteal cells, the relative effectiveness of the growth factors suggests a functional preference of Smad2 for activation by activin and Smad3 for activation by TGFb in GCs (Xu et al 2002). Schmierer et al (2003) reported that activin A signaling induces Smad2 but not Smad3 in GCs from the avian ovary. Consistent with differential expression of Smad2 and Smad3 in the ovary, there also seems to be functional differences in their regulation of key events related to follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…Activin receptors are expressed by theca cells, granulosa cells, and the oocyte, and binding of activin A to its receptor on these cells enhances preantral follicle growth and granulosa cell proliferation (13,14). Activin A treatment of avian granulosa cells not only leads to phosphorylation and nuclear translocation of Smad 2 and 3 but even increased Smad2 expression (15). Smad3 expression was found to be unchanged in that study, and Smad4 was not investigated.…”
mentioning
confidence: 93%